1993
DOI: 10.1159/000204473
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Recombinant Alfa-2a-lnterferon: A Feasible Maintenance Therapy in Acute Myeloid Leukaemia in the Older Patient

Abstract: Eleven patients with acute myeloid leukaemia (AML) in first complete remission (CR) were treated with alfa-2a-interferon (for short ‘interferon’) maintenance therapy, at a dose of 3 MU twice to thrice weekly subcutaneously. Adjustments were made to maintain neutrophil counts > 1 × 109/1 and platelet counts > 100 × 109/1· A transient fall in haemoglobin, neutrophil and platelet counts was noted in all 9 evaluable patients. Median time to nadir was 7 weeks. Initial dosage reductions were ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…For these patients, further study is necessary on which preemptive interventions might be reasonable alternatives. Some studies observed that IFN-α may be a feasible maintenance therapy for patients with acute myeloid leukemia [4]. In addition, some studies reported that IFN-α exerts a relatively strong immunomodulatory effect and can kill acute myeloid leukemia cells by regulating T cell and natural killer cell functions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…For these patients, further study is necessary on which preemptive interventions might be reasonable alternatives. Some studies observed that IFN-α may be a feasible maintenance therapy for patients with acute myeloid leukemia [4]. In addition, some studies reported that IFN-α exerts a relatively strong immunomodulatory effect and can kill acute myeloid leukemia cells by regulating T cell and natural killer cell functions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…For these patients, further study is necessary on what other preemptive interventions might be reasonable. Some studies observed that interferon‐alpha (IFN‐α) may be a feasible maintenance therapy for AML patients , and could exert a relatively strong immunomodulatory effect . In addition, Singhal et al , Gesundheit et al , and Tang et al reported that IFN‐α could induce a graft‐versus‐leukemia effect in patients with acute leukemia, and that patients who had relapsed after allo‐HSCT achieved complete remission (CR) on this treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Interferon (IFN) was used as early as the 1960s for AML treatment and showed some effects in both remission induction and salvage treatment for relapse after HSCT [2][3][4]. Our previous clinical observations found that the combination of thalidomide and IFN had certain effects for the treatment of relapsed or refractory AML [5].…”
mentioning
confidence: 99%